Perubahan Tutupan Hutan: Studi Kasus Sumatra Barat - Afdhal, Taufiq; Wibisono, Hariyo Tabah; Aadrean, Aadrean (Universitas Andalas, 2025)
The expansion of agricultural and plantation areas, and demands for improved accessibility, particularly on gentler slopes, has accelerated deforestation in West Sumatera. This study investigates changes in forest cover in West Sumatera over the period from 2000 to 2050, using two initial cover datasets from 2000 and 2015. We used driving variables, including elevation, slope, and roads, processed through the Change Modeller in IDRISI TerrSet. Modelling results indicate that forest cover changes are significantly influenced by topography, with gentler slopes experiencing faster rates of deforestation compared to steeper areas. Regions with flat land and easy access are particularly vulnerable to large-scale conversion for agricultural use, especially for palm oil plantations. The results underscore the interplay between infrastructure development and forest cover changes, highlighting the need for careful consideration of environmental impacts in planning and policy making. This study urges the policymakers to implement strategic spatial planning and land-use monitoring to mitigate impacts of deforestation to ensure forest sustainability in West Sumatera.